Pseudo-intellectualism and Melancholy. The Poetics of Black Bile in Lucian’s Lexiphanes - Kazantzidis, George (Araucaria, 2019)
In Lucian’s highly competitive and exhibitionist world, hyper-Atticism, the (ab)use of recondite, archaic words for the sake of impression, has become a sort of plague. In this article, I discuss how Lexiphanes focuses precisely on the literal and metaphorical associations of hyper-Atticism as a disease, by paying particular attention on the medical verdict - articulated in the text by Lucian’s authorial double, Lycinus - that the dialogue’s eponymous character suffers from melancholia. Rather than constitute a passing reference to the colloquial vocabulary of insanity, melancholia, I argue, helps Lucian forcefully assimilate the accumulation of pretentious words to the raving of the insane, a non-sensical blabbering that is void of meaning. At the same time, Lucian aims also to expose the presence of melancholy in the cultural and medical idiom of his time as a disease that typically affects ’great spirits’, people of exceptional intelligence. By calling Lexiphanes ’melancholic’, Lucian scolds Lexiphanes’ pretentiousness both as a hyper-Atticist and, no less importantly, as a pseudo-intellectual who is shaping his public image, temperamentally and physiognomically, as a genius whose atrabilious constitution entitles him to act and speak in strange ways.